The analysis of road infrastructure development financing in Lithuania - Lingaitiene, Olga (Transport, 2006)
The article describes major problems associated with the development of the Lithuanian roads, the priority areas and distribution of investments. The analysis performed and the calculations of investments into roads made for the last two years and the current year as well as graphical expression of the dynamics are presented and the conclusions are given. First Published Online: 27 Oct 2010